2016
DOI: 10.1080/08870446.2016.1185523
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting self-regulatory techniques to promote physical activity in older adults: null-findings from a randomised controlled trial

Abstract: A possible explanation for this null-finding in line with a recent meta-analysis is that some self-regulatory BCTs may be ineffective or even negatively associated with PA in interventions for older adults as they are assumed to be less acceptable for older adults. This interpretation was supported by observed reluctance to participate in self-regulatory BCTs in the current study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
69
0
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(82 citation statements)
references
References 54 publications
3
69
0
10
Order By: Relevance
“…Michie, Abraham, Whittington, McAteer and Gupta (2009) found techniques such as self-monitoring, prompting intention formation, goal setting, and feedback to be most effective in promoting PA. For French, Olander, Chisholm and McSharry (2014), however, self-monitoring and goal setting were shown to be less effective. Similar findings were shared recently by Warner, Wolff, Ziegelmann, Schwarzer and Wurm (2016) who found participants to not engage in planning and self-monitoring. With regards to the quantity of techniques, it has been found that interventions including more than one technique are more effective than those utilising just one strategy (Gilinksky et al, 2015;Michie et al, 2009;Williams & French, 2011).…”
Section: Effective 'Behavioural' Techniquessupporting
confidence: 71%
“…Michie, Abraham, Whittington, McAteer and Gupta (2009) found techniques such as self-monitoring, prompting intention formation, goal setting, and feedback to be most effective in promoting PA. For French, Olander, Chisholm and McSharry (2014), however, self-monitoring and goal setting were shown to be less effective. Similar findings were shared recently by Warner, Wolff, Ziegelmann, Schwarzer and Wurm (2016) who found participants to not engage in planning and self-monitoring. With regards to the quantity of techniques, it has been found that interventions including more than one technique are more effective than those utilising just one strategy (Gilinksky et al, 2015;Michie et al, 2009;Williams & French, 2011).…”
Section: Effective 'Behavioural' Techniquessupporting
confidence: 71%
“…While high profile studies and reviews report that social contact and support were important facilitators of participation in PA, particularly relevant to ageing populations [66,73,74,77], we were not able to confirm this effect with certainty. Indeed, a strategy involving planning of social support seemed counter-effective in promoting PA.…”
Section: Discussionmentioning
confidence: 59%
“…Our findings support the conclusions drawn by French and co-authors [35], who additionally ponder if self-regulatory BCTs may be too complex in circumstances of declining functioning. A recent large RCT examined the questionable benefits of self-regulatory techniques [77] and proposed ways of personalising interventions to the ageing population needs by mapping specific BCTs onto the physical capabilities and utilising a more flexible approach. Warner et al [77] argue that it might be appropriate to decrease the cognitive burden of self-regulatory tasks and emphasise physical activities as opportunities to experience positive affect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations